Footprints in Time: The Longitudinal Study of Indigenous Children: Report from Wave 4 - Footprints in Time Team (My University, 2013)
Footprints in Time is the name given to the Longitudinal Study of Indigenous Children, an initiative of the Australian Government. The study is conducted by the Department of Social Services (DSS) under the guidance of the Footprints in Time Steering Committee, chaired by Professor Mick Dodson AM. The study aims to improve the understanding of, and policy response to, the diverse circumstances faced by Aboriginal and Torres Strait Islander children, their families and communities. This report is the fourth in a series of reports produced for each wave of the data collection. The report provides a selection of research findings from wave 4. The range of topics covered in this report showcases both the richness of the data and the potential for further research. Further information about the study, including the fieldwork methodology and attrition rates, is available in the appendices. Readers may wish to refer to the previous reports for more detailed information about the developmental phase of the study and for results from the first three waves.
Keywords: Surveys and Survey Methodology; Children -- Indigenous; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Children; Indigenous; Surveys and Survey Methodology